Gonadal steroidogenesis in response to estradiol-17ß administration in the sea bream (Sparus aurata L.) - Condeça, João B. (2014)
The sea bream (Sparus aurata) is a protandrous hermaphrodite teleost fish in which estrogen administration induces testicular regression without influencing ovarian development. To analyze the changes in steroidogenesis of fish treated with two levels of estrogen (2 and 10 mg z kg21) and untreated control fish, fragments of gonads were incubated with tritiated 17-hydroxyprogesterone and the metabolites identified. The ability to extract radioactivity decreased with incubation time and was lower in gonads containing a larger proportion of ovarian tissue. The difference in steroidogenic capacity between control and estrogen-treated groups was generally quantitative rather than qualitative and paralleled the observed histological changes. The same metabolites were identified in all three groups, but estrogen treatment caused a marked inhibition of 5b-reduction, 3a-reduction, side-chain cleavage, and 11b-hydroxylation. The main androgens identified were 11b-hydroxy-4-androstene-3,17-dione and 3a-hydroxy-5b-androstane-3,17-dione, and the synthesis of both steroids was inhibited by estrogen treatment. Of the more polar pregnanes, 5bpregnane-3a,17,20a-triol and 5b-pregnane-3a,17,20btriol were detected in significant amounts, but only the latter appeared to be associated with development of the testis (in the untreated fish). A feature of sea bream gonadal steroidogenesis less common in other teleosts was the presence of 6a- and 6b-hydroxylation.